PERAN KEPALA SUKU DALAM MENJAGA EKSISTENSI HUKUM ADAT TERHADAP KEJAHATAN PENCURIAN DI HUTAN ADAT IMBO PUTUI DESA PETAPAHAN KECAMATAN TAPUNG KABUPATEN KAMPAR - Iga Arsita; Rika Lestari; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Indigenous peoples still use their customary laws in resolving crimes andviolations that occur in customary areas, especially crimes in theft that occur incustomary forbidden forests. The purpose of writing this thesis is first, to find outthe role of the tribal chief in maintaining the existence of customary law againstcrimes of theft in the imbo putui customary forest, Petapahan Village, TapungDistrict, Kampar Regency. Second, how is the application of customary sanctionsagainst crimes of theft in the customary forest of Imbo Putui, Petapahan Village,Tapung District, Kampar Regency.This type of research uses sociological or empirical legal researchmethods. This research was conducted in Petapahan Village, Tapung District,Kampar Regency, Riau Province. While the population and sample are all partiesrelated to the problems studied in this study, the data sources used are primarydata, secondary data and tertiary data, data collection techniques in this studyare interviews and document studies.The results of this study indicate that the important role of the tribal chiefis in maintaining the existence of customary law against crimes of theft incustomary forests and the application of customary sanctions against crimes oftheft in Imbo Putui customary forests because the perpetrators of theft assumethat the forest belongs to all people who know the forest, so the perpetrators donot know the customary law that applies in the area of the indigenous people ofPetapahan Village. The author's suggestion is for the nagari government and itsinstruments to improve oversight of the customary prohibition forest and makenagari regulations that regulate all categories of theft, so that not only timbertheft but everything that can be said to be theft is regulated in the nagariregulations and work together with local government authorities to conductoutreach to the community, so that the community knows that customary law inPetapahan Village still exists today and will not fade with the times.Keywords: The Role of the Head of the Tribe - Customary Law - ForestProhibition of Customs - Theft